A contribuição do Conselho da Mulher de Sorocaba para a efetivação da igualdade de direitos e oportunidade para as mulheres - Barros, Emanuela Oliveira de Almeida (2021)
This dissertation had as general objective to explain the memories of the contribution of the Municipal Council for Women's Rights of Sorocaba to the realization of equal rights and opportunities for women, considering the intersectionality of gender, class, race and sexuality. As specific objectives, the work sought to understand: 1) - The History of the Creation of Women's Councils in Brazil, 2) - Understand how the institutionalization of the women's movement took place and the importance of municipal councils for women's rights; 3) - Learn the history of the Municipal Council for Women's Rights in Sorocaba (Conselho dos Direitos da Mulher de Sorocaba) from the memories of the women who participated in the council. To unravel the proposed questions and point out possible answers, I opted for the oral history methodology. Starting from the following questions: why is it important to listen to the memories of the women who made the history of this council? Why is it important to hear them evoking their lived memories through their narratives? Thus, from these questions, I tried to unravel the scenario in which the remarkable events in the struggle for women's rights in the city of Sorocaba developed, which also express fragments of the struggle for women's rights in Brazil and around the world. By listening to the memories of the women who made the history of this council from 1984 to 2020, I was certainly able to unravel the scenario in which struggles, disputes, frustrations, the limits imposed on the women's movement developed and understand what makes the council a important political field of intervention, constituting a center that remains for debates on gender issues, and also the mechanism for the implementation of public policies for this same segment.